2012
DOI: 10.1111/j.1365-2044.2011.06998.x
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthetists’ risk assessment of placebo nerve block studies using the SHAM (Serious Harm and Morbidity) scale

Abstract: SummaryThe SHAM (Serious Harm and Morbidity) scale was developed to categorise the severity of potential complications of placebo control interventions in the context of local anaesthesia research. A convenience sample of 43 anaesthetists used the SHAM scale to grade ten published randomised controlled trials investigating local anaesthesia nerve blocks. The Fleiss j statistic assessed agreement between these anaesthetists and probability of random agreement (Pr(e)) when using the SHAM scale; a j > 0 shows con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 21 publications
(47 reference statements)
0
9
0
1
Order By: Relevance
“…Abdallah et al randomization method, allocation concealment, use of noninvasive sham blocks, 55,56 and the blinding of patients, anesthesiologists providing clinical care, and assessors. Our assessment of the success of patient blinding indicated that it was successfully maintained.…”
Section: Subomohyoid-suprascapular Versus Interscalene Blockmentioning
confidence: 99%
“…Abdallah et al randomization method, allocation concealment, use of noninvasive sham blocks, 55,56 and the blinding of patients, anesthesiologists providing clinical care, and assessors. Our assessment of the success of patient blinding indicated that it was successfully maintained.…”
Section: Subomohyoid-suprascapular Versus Interscalene Blockmentioning
confidence: 99%
“…Some of the included studies may raise ethical concerns since they worked with invasive placebo (so-called shamcontrol). The SHAM (serious harm and morbidity) scale classifies the risk of saline injection as placebo control of TAP block as highest (grade 4) [55].…”
Section: Very Low Certaintymentioning
confidence: 99%
“…The Serious Harm and Morbidity (SHAM) score is used to grade the severity of potential complications of placebocontrolled interventions in local anaesthesia research and it is, perhaps, of note that pneumothorax is listed as a potential complication with a grade 4 SHAM score, which represents a major risk. 3 In order to perform TPVB while minimizing the risk of pneumothorax, the clinician must have the relevant anatomical knowledge. The present study aimed to identify the depth of needle insertion required to reach the paravertebral space, and the distance from the spinous process to the insertion point on the skin, using chest computed tomography (CT) scanning of paediatric patients.…”
Section: Introductionmentioning
confidence: 99%